POLICY IMPLEMENTATION OF STATE APPARATUS POSTGRADUATE STUDY PROGRAM - Nenobais, Harry; Laviandhy, Debby Arthi; Hakim, Arief Rahman (Moestopo International Review on Social, Humanities, and Sciences, 2025)
By taking a case study at the Ministry of Agriculture, this journal aims to obtain an overview of the extent to which the implementation of the Postgraduate Study Task Program Policy for ASN is running and has a particular impact on efforts to improve the quality of ASN human resources. Technically, the implementation of learning tasks is regulated by each government institution based on Permenpan RB number 4 of 2013. Although the said policy has been implemented, in its implementation there are various challenges that must be considered. By using a qualitative approach, this research focuses on the participants of the study assignment at several partner universities of the Ministry of Agriculture. By referring to the policy implementation model approach, the research results generally illustrate that the master and doctoral study assignment policies within the Ministry of Agriculture have been able to accommodate various important things needed for the success of policy implementation. However, there are several important challenges that must be considered in order to strengthen the learning assignment policy in the future.